Behavioral marketing : delivering personalized experiences at scale - Walters, Dave, 1968- (Wiley, 2015)
"This book focuses on fixing marketers' highly inefficient processes and spotty results and describes how to be more "revenue predictable". The book explains the key principles of behavioral marketing, which include: customer journey mapping, channel-level planning, data capture and hygiene, campaign creation, delivery best practices, and measurement/optimization. It will include up to 10 case studies across multiple industries highlighting the revenue growth and process efficiencies resulting from great behavioral-driven marketing."--